Well-being and academic achievement in secondary school pupils: The unique effects of burnout and engagement - Cadime, Irene Maria Dias (2016)
The main goal of this study was to examine the relationship among burnout, engagement, well-being, and academic performance in Portuguese secondary school pupils. The existence of gender related differences in these relationships was also investigated. The sample was composed of 489 pupils who attended an academic track at secondary school. Results of multi-group structural equation modelling indicated that higher levels of cynicism towards studies were associated with lower academic achievement. Exhaustion was not uniquely related to the adolescents' academic achievement or well-being. However, higher levels of engagement, namely dedication and vigour, were related to higher levels of wellbeing. Moreover, vigour was also uniquely associated with academic achievement. The results were similar for boys and girls. Implications for intervention and future research are discussed. (C) 2016 The Foundation for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.